Keperawatan Wisatawan Pantai untuk Meningkatkan Keselamatan Wisatawan di Tempat Wisata - Komang Ayu Henny Achjar (Politeknik Kesehatan Tanjung Karang, 2020)
Coastal tourist nursing takes an important role in managing health in coastal communities order. The improvement of accidents while traveling can occur due to natural phenomena and the negligence of tourists and lifeguards. Through the implementation of the coastal tourist nursing model, tourist safety can be improved by empowering lifeguards and community nurses as well as representing a multi-sectoral partnership between health-sector other sectors. This study used a quasi-experimental pre-post-test design with a control group and involved 118 lifeguards and 720 tourists. Sampling used the Cluster Sampling technique which was carried out on the coasts of Badung Regency. Data were analyzed with the chi-square test, t-test, and General Linear Model-Repeated Measure (GLM-RM). Measuring the safety of tourists using the benchmarks of knowledge, attitudes, and actions of tourists who studied with a questionnaire with the results of the validity test r-count>0,361 and reliability test with r-Alpha for knowledge 0,870, attitude 0,888, and behavior 0,915. The increase was significant (p-value<0,05) in all aspects of tourists in the intervention group after 3 months of giving the intervention model. However, tourist safety tended to decrease after 6 months of intervention. Strengthening the implementation of models and communication between lifeguards and community nurses is needed to maintain community safety in specific coastal groups.